The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/ijc.31603
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II trial of pimasertib plus gemcitabine in patients with metastatic pancreatic cancer

Abstract: The selective MEK1/2 inhibitor pimasertib has shown anti-tumour activity in a pancreatic tumour model. This phase I/II, two-part trial was conducted in patients with metastatic pancreatic adenocarcinoma (mPaCa) (NCT01016483). In the phase I part, oral pimasertib was given once daily discontinuously (5 days on/2 days off treatment) or twice daily continuously (n = 53) combined with weekly gemcitabine (1,000 mg/m ) in 28-day cycles to identify the recommended phase II dose (RP2D) of pimasertib. In the phase II p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 33 publications
3
49
0
Order By: Relevance
“…34 A phase I/II randomized trial of the combination MEK inhibitor pimasertib/gemcitabine versus gemcitabine did not supported further development of this combination in a first-line treatment of metastatic pancreatic cancer. 35 Interestingly, our data…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…34 A phase I/II randomized trial of the combination MEK inhibitor pimasertib/gemcitabine versus gemcitabine did not supported further development of this combination in a first-line treatment of metastatic pancreatic cancer. 35 Interestingly, our data…”
Section: Discussionmentioning
confidence: 53%
“…Actually, a phase II randomized clinical trial in patients with metastatic PC showed that the combination of the MEK inhibitor trametinib with gemcitabine did not improve overall survival, disease‐free survival, overall response rate or duration of response in comparison to gemcitabine alone . A phase I/II randomized trial of the combination MEK inhibitor pimasertib/gemcitabine versus gemcitabine did not supported further development of this combination in a first‐line treatment of metastatic pancreatic cancer . Interestingly, our data show that MEK inhibition could be of potential interest only after progression on gemcitabine and in the subtype of mesenchymal pancreatic tumor cells.…”
Section: Discussionmentioning
confidence: 66%
“…Induction of MAPK activity is a well-established mechanism that allows cancer cells to endure genotoxic stress (48). However, MEK inhibitors fail to potentiate chemotherapy in pancreatic cancer (49,50), suggesting that targeting MAPK alone is insufficient, or that compensatory escape mechanisms such as enhanced NF-κB activity should be cotargeted. Similarly, in a prostate cancer model, addition of an NF-κB pathway inhibitor significantly potentiates the antitumor effect of MEK inhibitors (51).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%
“…Colorectal Cancer [14] , pancreatic cancer [15] . Since now there are a few reports about MEK inhibitor (arm A, D) or irinotecan (arm B, C) [16] .…”
Section: Discussionmentioning
confidence: 99%